Targeting the Pim kinases in multiple myeloma - Keane, Niamh A.; Raab, Marc-Steffen (Blood cancer journal, 2015)
Multiple myeloma (MM) is a plasma cell malignancy that remains incurable. Novel treatment strategies to improve survival are urgently required. The Pims are a small family of serine/threonine kinases with increased expression across the hematological malignancies. Pim-2 shows highest expression in MM and constitutes a promising therapeutic target. It is upregulated by the bone marrow microenvironment to mediate proliferation and promote MM survival. Pim-2 also has a key role in the bone destruction typically seen in MM. Additional putative roles of the Pim kinases in MM include trafficking of malignant cells, promoting oncogenic signaling in the hypoxic bone marrow microenvironment and mediating resistance to therapy. A number of Pim inhibitors are now under development with lead compounds entering the clinic. The ATP-competitive Pim inhibitor LGH447 has recently been reported to have single agent activity in MM. It is anticipated that Pim inhibition will be of clinical benefit in combination with standard treatments and/or with novel drugs targeting other survival pathways in MM.
Gesehen am 07.07.2020